The Fibrinolytic System in Peripartum Depression - Hoirisch-Clapauch, Silvia (Seminars in Thrombosis and Hemostasis, 2022)
The relationship between depression and reduced fibrinolytic activity reflects the role of tissue plasminogen activator and plasmin in brain remodeling underlying resilience, depression remission, and reward processing, rather than the dissolution of fibrin clots. Individuals who experience depression demonstrate hippocampal and prefrontal cortex atrophy, as well as impaired neuronal connectivity. Brain-derived neurotrophic factor (BDNF), synthesized as a precursor that is activated through cleavage by tissue plasminogen activator and plasmin, influences adult neurogenesis and neuronal plasticity in the hippocampus and prefrontal cortex. Depression is associated with decreased brain levels of BDNF, due to reduced activity of tissue plasminogen activator and plasmin. Tissue plasminogen activator and plasmin also mediate the release of dopamine, a neurotransmitter implicated in motivation and reward. Peripartum depression defines a depressive episode that occurs during pregnancy or in the first month after delivery, reinforcing the concept that postpartum depression may be a continuum of antenatal depression. This article describes the fibrinolytic status in the healthy brain, in stress and depression, emphasizing the links between biological markers of depression and defective fibrinolysis. It also discusses the association between hypofibrinolysis and risk factors for perinatal depression, including polycystic ovary syndrome, early miscarriage, preeclampsia, stressful life events, sedentariness, eating habits, gestational and type 2 diabetes, and antithyroid peroxidase antibodies. In addition, it reviews the evidence that antidepressant medications and interventions as diverse as placebo, psychotherapy, massage, video game playing, regular exercise, dietary modifications, omega 3 fatty acid supplementation, neurohormones, and cigarette smoking may reduce depression by restoring the fibrinolytic activity. Last, it suggests new directions for research.
Keywords: adverse pregnancy outcomes; antidepressants; diet; exercise; lifestyle interventions; peripartum depression; risk factors; tissue plasminogen activator; videogame playing